Familiarity of medical residents at Kerman Medical University with evidence based medicine databases - Masoumeh Sadeghi; Narges Khanjani; Fatemeh Motamedi; Maryam Saber; Gholamreza Sharifi Rad (Journal of Research in Medical Sciences, 2011)
Background: Using Evidence Based Medicine (EBM) in clinical practice is an important strategy for improving and updating medical services. Therefore, EBM has recently attracted a lot of attention in many medical schools around the world. In this study we tried to evaluate the familiarity of clinical residents who are one of the main clinical decision makers in public hospitals and also the next generation of specialists with EBM and EBM databases. Methods: This was a cross-sectional study in 2010 in which clinical residents of Kerman Medical University (KMU) participated. Residents were asked about the four main EBM databases. The data was collected by a self-administered questionnaire. Results: The data showed that from the respondents only 26.6% knew about EBM and only 28.7% of the respondents were familiar with "Up to Date", 22.3% were familiar with "Ovid EBM Reviews", 6.4% were familiar with "Cochrane" and 5.3% were familiar with "BMJ Clinical Evidence". The frequencies of those that actually used the databases for clinical decision making and could answer the search questions were even less. Conclusions: The results showed most of the residents lack sufficient knowledge about EBM and its databases. The reason is probably the inexistence of a systematic and comprehensive curriculum for EBM education during their residency program or undergraduate program. Thus, due to the importance of learning EBM in this group, there is a necessity to plan a comprehensive and proper education schedule for EBM and EBM database use at the beginning or further stages of residency.